2019
DOI: 10.1371/journal.pbio.3000046
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuned adaptation of embryo–endometrium pairs at implantation revealed by transcriptome analyses in Bos taurus

Abstract: Interactions between embryo and endometrium at implantation are critical for the progression of pregnancy. These reciprocal actions involve exchange of paracrine signals that govern implantation and placentation. However, it remains unknown how these interactions between the conceptus and the endometrium are coordinated at the level of an individual pregnancy. Under the hypothesis that gene expression in endometrium is dependent on gene expression of extraembryonic tissues and genes expressed in extraembryonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…For example, ADH5 was not identified by trehalose method (MD_CE/TRE) but with relatively high intensity in all three replicates of MC in the comparison ME vs. MC. ADH5 gene expression has been found in intercaruncular tissues in bovine [ 70 ] and also identified in the uterine fluid proteome of roe deer [ 71 ], where it may play a role in cellular detoxification before implantation. Besides, the use of trehalose in the EVs isolation protocol allowed or improved the identification of other proteins including PAK2, LAMB2 and SEMA4B, which may play an important role in uterine functions and embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ADH5 was not identified by trehalose method (MD_CE/TRE) but with relatively high intensity in all three replicates of MC in the comparison ME vs. MC. ADH5 gene expression has been found in intercaruncular tissues in bovine [ 70 ] and also identified in the uterine fluid proteome of roe deer [ 71 ], where it may play a role in cellular detoxification before implantation. Besides, the use of trehalose in the EVs isolation protocol allowed or improved the identification of other proteins including PAK2, LAMB2 and SEMA4B, which may play an important role in uterine functions and embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from multiple mammalian species indicates that the endometrium is capable of mounting an implantation response tailored to the developmental potential of individual embryos. 21,[51][52][53] In humans, directed migration of decidualizing EnSC and active encapsulation of the conceptus constitutes an important initial step in the implantation process. 52 In vitro studies demonstrated that high-quality human embryos stimulate migration of decidual cells, whereas low-quality embryos fail to do so.…”
Section: Discussionmentioning
confidence: 99%
“…21,[51][52][53] In humans, directed migration of decidualizing EnSC and active encapsulation of the conceptus constitutes an important initial step in the implantation process. 52 In vitro studies demonstrated that high-quality human embryos stimulate migration of decidual cells, whereas low-quality embryos fail to do so. Conversely, migration of undifferentiated EnSC is actively inhibited by high-quality embryos, but not low-quality embryos.…”
Section: Discussionmentioning
confidence: 99%
“…21,4850 In humans, directed migration of decidualizing EnSC and active encapsulation of the conceptus constitutes an important initial step in the implantation process. 49 In vitro studies demonstrated that high-quality human embryos stimulate migration of decidual cells whereas low-quality embryos fail to do so. Conversely, migration of undifferentiated EnSC is actively inhibited by high-quality embryos, but not low-quality embryos.…”
Section: Discussionmentioning
confidence: 99%